PENGARUH RASIO KEUANGAN TERHADAP KEMAMPUAN MEMPREDIKSI PERUBAHAN LABA PADA PERUSAHAAN-PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI PT BURSA EFEK JAKARTA - SW, Suprihatmi (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2006)
ABSTRACT The purpose of this research is to find the influences of financial ratio toward the ability to predict the changing profit on manufacture firms which are listed in PT. Bursa Efek Jakarta. These financial ratio includes Debt to Equity, Leverage Ratio, Gross Profit Margin, Net Operating Margin, Inventory Turnover, Total Assets Turnover, Return On Investment, Return On Equity and profit which used is before tax profit. The analysis technique which use is multiple regression sampling, t-test, F-test and R square. From the result we found 4 out of 8 factors which involves to the changing profit ratio, there are Gross Profit Margin, Inventory Turnover, Return On Investment, Return On Equity but simultaneously the financial ratio variables influences the profit changing. This means the hypothesis which is state that there is any influences on financial ratio toward the ability to predict the profit changing are proven. Keywords: Financial ratio, changing profit, manufacture firms, Bursa Efek Jakarta